Síntese e caracterização dielétrica de filmes finos de Bi3NbO7 obtidos pelo método dos precursores poliméricos - Romão, Rafael da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Bi3NbO7 thin films were prepared by the polymeric precursor method. The precursor solutions were prepared with excess of bismuth ranging from 0% to 10% and the pH was controlled to be maintained between 8 and 9. This control was done by adding to the solution niobium and ethylene glycol. The final solution was clear and free of precipitation. After obtaining the precursor solution, has begun the process of characterization of powders with thermogravimetry (TG), differential thermal analysis and X-ray analysis (XRD). The films were obtained by the polymeric precursors, the method is advantageous because it is simple, and low cost involves steps and controlled stoichiometry. The films were annealed and characterized by XRD and SEM and also characterized according to their dialectics properties. We observed that the best results were obtained when the film is thermally at 800 ° C for two hours and 860 ° C for two hour. Under these conditions we obtain Bi3NbO7 thin films with good homogeneity, uniform distribution of the grains, but with the formation of secondary phase, which does not occur in treatments with lower temperature. The dielectric characterization showed that the produced film showed good characteristics with high dielectric constant and low loss

Filmes finos de Bi3NbO7 foram preparados pelo método dos precursores poliméricos. As soluções precursoras foram preparadas com excesso de bismuto variando de 0% até 10% e o pH foi controlado a fim de ser mantido entre 8 e 9. Esse controle foi feito adicionando à solução Nb e Etilenoglicol. A solução final foi límpida e sem precipitação. Após obter a solução precursora, deu-se início ao processo de caracterização dos pós com termogravimetria (TG), analise térmica diferencial e análise por raios-X (DRX). Os filmes foram obtidos pelo Método dos Precursores Poliméricos; o método é vantajoso, pois é simples, envolve etapas de baixo custo e estequiometria controlada. Os filmes obtidos foram tratados termicamente e caracterizados pelo DRX e MEV e caracterizados também quanto às suas propriedades dieléticas. Observamos que os melhores resultados foram obtidos quando se trata termicamente os filmes em 800°C por duas horas e 860°C por uma hora. Nessas condições obtemos filmes finos de Bi3NbO7 com boa homogeneidade, uma distribuição uniforme dos grãos, porém com a formação de fase secundária, fato que não ocorre nos tratamentos com temperatura menor. A caracterização dielétrica mostrou que o filme produzido apresentou boas características, com alta constante dielétrica e baixa perda
Keywords: Filmes finos; Dieletricos